Safety of Endoscopic Transsphenoidal Pituitary Surgery during the COVID-19 Pandemic and Comparison to the Pre-Pandemic Era - Amarouche, Meriem; Rashid, Samin; Eraifej, John; Borg, Anouk; Halliday, Jane; Warner, Orlando J.; Cudlip, Simon A. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective The COVID-19 pandemic has caused significant disruption to the surgical care of patients with pituitary tumors. Guidance issued early during the pandemic suggested avoiding transnasal approaches to minimize risks of transmitting COVID-19 to health care professionals involved in these procedures.Methods This observational, single-center study compares results of endoscopic transsphenoidal approach (TSA) for pituitary tumors since the start of the pandemic to a pre-pandemic period. Anesthetic time, surgical time, and complication rates were compared. Newly acquired COVID-19 infections and transmission rates to patients and staff were reviewed. Data were analyzed by using the independent t-test, Mann–Whitney U test, and Pearson Chi-square test, significance set at p <0.05.Results Over a 12-month period, a total of 50 and 69 patients underwent endoscopic TSA for pituitary tumor during and before the pandemic, respectively. All patients tested negative for COVID-19 preoperatively. Median duration of anesthesia was 35 minutes (interquartile range [IQR]: 22) during the pandemic and 25 minutes (IQR: 8, p = 0.0002) pre-pandemic. Median duration of surgery was 70 minutes (IQR: 28) during the pandemic and 79 minutes (IQR: 33.75, p = 0.126) pre-pandemic. There were no statistically significant differences between intraoperative CSF leaks and complication rates. No staff members tested positive for COVID-19. Three patients tested positive for COVID-19 postdischarge, but the infections were community acquired.Conclusion In contrast to published guidelines, adequate preoperative testing, a multidisciplinary approach and the implementation of standardized protocols and vaccination against COVID-19 allow for endoscopic transsphenoidal surgery to be performed safely in patients with pituitary pathology during the pandemic.
Keywords: pituitary surgery; transsphenoidal; nonfunctioning pituitary adenoma; functioning pituitary adenoma; Rathke's cleft cyst; COVID-19 pandemic